Hakikat Belajar Menurut UNESCO Serta Relevansinya Pada Saat Ini - Ujang Hartono; Risal Qori Amarullah; Enday Mulyadi (Khidmatussifa: Journal of Islamic Studies, 2022)
Learning is an activity or a process to gain knowledge, improve skills, improve behavior, develop attitudes, and produce personality. Learning is said to be successful if a person is able to repeat the material he has learned, so this kind of learning is called rote learning, learning through memory, by heart, outside the head, regardless of meaning. As stated by UNESCO, education is based on four pillars, namely, learning to know, learning to do, learning to live together, and learning to be. Of course, in these pillars, it does not only stop at the cognitive aspects but the affective and psychomotor This research uses a qualitative approach and uses a descriptive analytic method, which is very closely related to the qualitative approach, and in this study, the authors take qualitative data types. The data analysis technique that was carried out was by distributing questionnaires in the form of four essay questions. This was done to determine the relevance of Learning According to UNESCO at the moment. The results from the answers of the informants at STIT Sirojul Falah Bogor found that by learning to know there is relevance to life, meaning that by knowing knowledge it can be applied in life; by learning to do, the resource persons believe that there is relevance between knowledge and work in this life; they answer that knowledge is not just known but needs to be actualized in life; by learning to live together, it is found that resource persons can understand the basic tasks of social life in their community, so that with this knowledge individuals can be well received in society; with learning to be, there is relevance to life, meaning that by